ANALISIS WISATA KULINER KOTA BUKITTINGGI - Julita Pratiwi; Rahmanelli rahmanelli (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
The purpose of this research is to describe and analyze the culinary tourism of Bukittinggi city based on accessibility, price and comfort. This type of research is quantitative descriptive research. The research site is located in Bukittinggi city with the population is the end of the tourism city of Bukittinggi amounted to 62,996 people. Sampling uses purposive sampling techniques with a sample number of 100 people. Data collection techniques are observation, questionnaire, and documentation. The data analysis technique used is percentage. This study found that(1) Analysis of culinary tourism based on accessibility, namely road conditions show variants including good (17.08%), moderate (73.26%), damaged (5.71%), severely damaged (3.95%), generally having road conditions in the form of asphalt and concrete which make it easier for motorists to pass through. (2) Analysis of culinary tourism based on prices finds a tendency of culinary tourists who consider that culinary prices are still categorized as expensive (8-15). (3) Analysis of convenience-based culinary tourism includes a fairly good category (quite comfortable) (8-15).